2007
DOI: 10.1007/s10562-007-9265-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient H2 Production from Ethanol over Mo2C/C Nanotube Catalyst

Abstract: Mo 2 C deposited on silica is an effective catalyst for the decomposition of ethanol; the extent of the reaction approached 100% even at 623-673 K. Beside H 2 several C-containing compounds were produced, which caused the low yield of hydrogen. Preparation of Mo 2 C by the reaction of MoO 3 with multiwall carbon nanotube, however, dramatically altered the product distribution. The formation of hydrogen came into prominence; about 40% of hydrogen content of ethanol decomposed at 523-723 K has been converted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…[20] DME is also considered as a potential fuel for the generation of hydrogen. [21][22][23][24][25][26][27][28] Recently, we reported that Mo 2 C prepared on carbon Norit is an effective and stable catalyst, not only in the reforming of ethanol [29,30] and methanol, [31,32] but also for the production of hydrogen from DME. [33] On 10 % Mo 2 C/Norit, complete conversion of dimethyl ether was attained at 873-923 K. Adding water to DME slightly improved the production of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…[20] DME is also considered as a potential fuel for the generation of hydrogen. [21][22][23][24][25][26][27][28] Recently, we reported that Mo 2 C prepared on carbon Norit is an effective and stable catalyst, not only in the reforming of ethanol [29,30] and methanol, [31,32] but also for the production of hydrogen from DME. [33] On 10 % Mo 2 C/Norit, complete conversion of dimethyl ether was attained at 873-923 K. Adding water to DME slightly improved the production of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic reaction was carried out at 1 atm of pressure in a fixed-bed, continuous flow reactor made of a quartz tube (8 mm id) [9,10]. The flow rate was in general 60 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Platinumgroup metals are the commonly used catalysts for the decomposition and reforming of alcohols [1][2][3][4][5][6]. Recently we found that Mo 2 C prepared by the reaction of MoO 3 with multiwall carbon nanotube and activated carbon Norit is also an excellent catalyst for the decomposition and reforming of oxygenated compounds such as methanol [7,8], ethanol [9,10] and dimethyl ether [11]. An important property of the Mo 2 C/C is its high stability, which means that the conversions and the H 2 yields decreased only by few percents even after 30-75 h of reaction at 673-773 K.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic reaction was carried out at 1 atm of pressure in a fixed-bed, continuous flow reactor made of a quartz tube (8 mm id) [21,22]. The flow rate was in general 40 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we reported that Mo 2 C prepared by the reaction of MoO 3 with multiwall carbon nanotube and activated carbon Norit is an excellent catalyst for the decomposition of ethanol to H 2 [21,22]. This solid was also effective in the decomposition/reforming of methanol [23] and dimethyl ether [24].…”
Section: Introductionmentioning
confidence: 99%